Broad and Long-Lasting Vision Improvements in Youth With Infantile Nystagmus After Home Training With a Perceptual Learning App - Huurneman, Bianca; Goossens, Jeroen (Frontiers in Neuroscience, 2021)
Current treatments for infantile nystagmus (IN), focused on dampening the oscillating eye movements, yield little to no improvement in visual functioning. It makes sense, however, to treat the visual impairments associated with IN with tailored sensory training. Recently, we developed such a training, targeting visual crowding as an important bottleneck in visual functioning with an eye-movement engaging letter discrimination task. This training improved visual performance of children with IN, but most children had not reached plateau performance after 10 supervised training sessions (3,500 trials). Here, we evaluate the effects of prolonged perceptual learning (14,000 trials) in 7-18-year-old children with IN and test the feasibility of tablet-based, at-home intervention. Results demonstrate that prolonged home-based perceptual training results in stable, long lasting visual acuity improvements at distance and near, with remarkably good transfer to reading and even stereopsis. Improvements on self-reported functional vision scores underline the clinical relevance of perceptual learning with e-health apps for individuals with IN.